2016
DOI: 10.1016/j.celrep.2016.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Polycomb-Group Protein EZH2 Leads to Compromised Self-Renewal and Differentiation Defects in Human Embryonic Stem Cells

Abstract: SummaryThrough the histone methyltransferase EZH2, the Polycomb complex PRC2 mediates H3K27me3 and is associated with transcriptional repression. PRC2 regulates cell-fate decisions in model organisms; however, its role in regulating cell differentiation during human embryogenesis is unknown. Here, we report the characterization of EZH2-deficient human embryonic stem cells (hESCs). H3K27me3 was lost upon EZH2 deletion, identifying an essential requirement for EZH2 in methylating H3K27 in hESCs, in contrast to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 64 publications
10
95
3
Order By: Relevance
“…2g) and pluripotent factors (Fig. 2h) were not influenced after EZH2 knockout [24], supporting that change of ACE2 expression was not caused by cell fate change. Taken together, our analysis indicated that presence of EZH2 impeded ACE2 expression.…”
Section: Ace2 Expression Was Upregulated Upon Ezh2 Knockout In Human supporting
confidence: 55%
See 1 more Smart Citation
“…2g) and pluripotent factors (Fig. 2h) were not influenced after EZH2 knockout [24], supporting that change of ACE2 expression was not caused by cell fate change. Taken together, our analysis indicated that presence of EZH2 impeded ACE2 expression.…”
Section: Ace2 Expression Was Upregulated Upon Ezh2 Knockout In Human supporting
confidence: 55%
“…Here, we chose human ESC as the model to study transcriptional regulation of ACE2, and found that ACE2 level was upregulated after EZH2 knockout and recovered to a similar level as control group after adding EZH2 back [24] (Fig. 2f).…”
Section: Ace2 Expression Was Upregulated Upon Ezh2 Knockout In Human mentioning
confidence: 99%
“…Because PRC2 has been shown to be a critical mediator of pluripotency in normal as well as cancer stem cells (26, 27), additional experiments were performed to examine expression of core components of this complex. qRT-PCR and immunoblot experiments (Figures 4A and 4B) demonstrated significant increases in EZH2 , EED and SUZ12 expression in Lu-iPSC relative to SAEC.…”
Section: Resultsmentioning
confidence: 99%
“…Suz12 is required for methyltransferase activity, silencing function as well as for PRC2 protein stabilization in somatic as well as in human ESCs (Cao and Zhang, 2004) (Pasini et al, 2004) (Collinson et al, 2016). Our experiments indicate that, in addition to associating with the H3K27 demethylases KDM6A (UTX) (Wang et al, 2013), KDM6B (JMJD3) and KDM7A (KIAA1718), the H3K36 methyltransferase SETD2 (Chen et al, 2012) and Ser2P-PolII (Yoh et al, 2007), Spt6 also interacts with Suz12 in ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…PRC2 is also required to maintain transcriptional repression of developmental regulators and for self-renewal of human ESCs (Collinson et al, 2016). Even though the individual core PRC2 subunits Ezh2, Suz12, and Eed are highly expressed (Shen et al, 2008), the chromatin of ESCs is partially refractory to H3K27me3.…”
Section: Introductionmentioning
confidence: 99%